Australis 4 learning: benefits and outcomes of a Second Life simulation for the automated assessment laboratory - Reiners, Torsten; Dreher, Heinz; Dreher, Naomi; Dreher, Carl; Kuhlenkampff, C. (Association for the Advancement of computing in Education (AACE), 2009)
Aim of the Automated Assessment Laboratory (AAL) being established at the School of InformationSystems (Curtin Business School) is to provide lecturers with the opportunity to have essays automatically assessed using MarkIT. So far, the process was described by using static and non-interactive media, causing misunderstanding or leaving open questions. To improve the understanding and acceptance of AAL, we decide on an interactive simulation, where everyone can chose their role in the system and experience every step in a given setup. For the 3D simulation, we created the Second Life Island Australis 4 Learning, where a virtual course guides the visitors through the AAL allowing to interact with other avatars as well as objects like drop boxes or presentation devices for the results. The results are summarized on a poster as shown in the following proposal.